Načrtovanje odpusta iz psihiatrične bolnišnice iz perspektive socialnih delavk - Seljak, Andreja (Socialno delo, 2022)
Planning discharge is the central task of social workers in a psychiatric hospital. Effective hospital discharge planning is a team process based on assessing needs and finding suitable responses to them. The research results show considerable inconsistency in this area, as the process of discharge planning is initiated at different times. It is especially the users’ poor health that does not allow their wishes and needs to be consistently considered, and prevents user participation and autonomy. Consequently, patronizing practices are inevitable. Being treated in a psychiatric hospital is still associated with considerable stigma. The research findings show that social workers feel as equal members of department teams and face plenty of ethical dilemmas at their work. Undergraduate studies have equipped social workers with a wide specter of theoretical and practical knowledge; however, they would like the study programme to be supplemented with health care topics.
Keywords: ethical dilemmas; etične dileme; health care; needs assessment; ocena potreb; psihiatrija; psychiatry; social work; socialno delo; team work; timsko delo; uporabniška participacija; user participation; zdravstvo